Manfaat Media Sosial Pada UMKM Apem Singkong Keju Pak Gede - Aisah A; Silvi Yulianingsih; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Technological progress is a challenge for Micro, Small and Medium Enterprises (MSMEs) to continue to survive. Information technology, especially social media, is very useful for MSMEs to improve their marketing. This industrial visit was conducted to identify the use of social media and its benefits to MSMEs in the West Karawang region. This industrial visit is an observational industrial visit with a descriptive method and combines it with interviews. This industrial visit aims to get an overview of the use of social media in MSMEs and its benefits for the development of MSMEs. The results of this industrial visit show that the most widely used social media are Facebook and WhatsApp, apart from social media, websites are also used by most MSMEs for marketing. Social media is an effective communication medium for MSMEs, can increase income Â and open resellers for consumers who want to resell these products. The use of social media can increase sales volume by more than 100% if done consistently and updating information every day. The conclusion from this industrial visit, social media has the potential to increase market share and sales volume, so it needs to be used optimally and consistently.Â